Comparison of Protein Energy Wasting Assessment on Quality of Life Regular Hemodialysis Patients - Ni Wayan Sri Wardani; Dewa Gde Agung Budiasa (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background. Protein energy wasting (PEW) is one of several markers of the quality of hemodialysis (HD) services in Indonesia, however not many studies conducted PEW assessement with quality of life (QoL) domain of regular HD patients. Aim: To determine comparison of PEW assessment with QoL domains in regular HD patients. Method: A Cross-sectional study with total sampling of 105 regular HD patients at Sanjiwani Gianyar General Hospital, on June to July 2022, The PEW assessments: body mass index (BMI), serum albumin, subjective global assessment (SGA), malnutrition inflammation score (MIS), and the International Society of Renal Nutrition and Malnutrition (ISRNM) with QoL domains by KDQOL-SF (Kidney Disease Quality of Life Short Form). Results.  Most of the subjects were men (54.2%), the mean age was51.66 years and mean duration of HD was 50.28 months. The mean of BMI, serum creatinine, and serum albumin were 23.46 kg/m2, 9.70 mg/dL, and 3.86 mg/dL respectively, and median MIS 5. This study obtained significant correlation of BMI and QoL domains: work status, physical functioning, role of physics, energy/fatigue, and SF 12 physical composite. The MIS also significantly correlated with emotional well-being, sleep, and burden of disease. And ISRNM significantly correlated with energy/fatigue, and sexual function, On logistic regression analysis, this study obtained that albumin was significantly related to general health, emotional well-being, and energy/fatigue, Conclusion: Assessment of PEW (BMI, serum albumin, MIS, SGA, and ISRNM ) were related to several domains of QoL.